2006
DOI: 10.1038/sj.leu.2404080
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic function and survival of natural killer cells are severely altered in myelodysplastic syndromes

Abstract: Natural Killer (NK) cells are critical in host defense against malignant transformation and are potent antileukemic cytotoxic effectors. In the present study, we investigated the peripheral NK function in patients with myelodysplastic syndromes (MDS). We demonstrated that the peripheral NK cell population was quantitatively normal in MDS patients. Furthermore, NK cells displayed an expression of the activating natural cytotoxicity receptors (NCR) NKp46 and NKp30 as well as NKG2D similar to that observed in don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 38 publications
5
98
2
3
Order By: Relevance
“…Collectively, our results provide novel conducted the first comprehensive analysis of peripheral blood NK cells in patients with MDS, and described a global defect in NK-cell cytotoxicity and proliferation that was not reflected by changes in surface expression of activating receptors. 28 Moreover, the functional defects were not restricted to specific subgroups of patients but extended to both low-and high-risk MDS. The poor function of NK cells was attributed to the fact that a proportion of the NK cells carried the same genetic alteration as the CD34 þ blast cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, our results provide novel conducted the first comprehensive analysis of peripheral blood NK cells in patients with MDS, and described a global defect in NK-cell cytotoxicity and proliferation that was not reflected by changes in surface expression of activating receptors. 28 Moreover, the functional defects were not restricted to specific subgroups of patients but extended to both low-and high-risk MDS. The poor function of NK cells was attributed to the fact that a proportion of the NK cells carried the same genetic alteration as the CD34 þ blast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating previous studies, CD56 dim NK cells from peripheral blood of MDS patients also showed reduced degranulation compared with cells from healthy donors, (Figures 3a and c). 25,28 Further, to more precisely investigate the capacity of surface receptors to elicit NK-cell degranulation, we used a previously described assay, in which NK cells were co-incubated with P815 cells preincubated with antibodies for specific NK-cell receptors. 31 These experiments revealed that degranulation induced by co-activation of either NKG2D or DNAM-1 in combination with 2B4 was reduced in CD56 dim NK cells from both bone marrow and peripheral blood of MDS patients, as compared with that of NK cells from healthy controls (Figures 3d and e).…”
Section: Impaired Nk-cell Degranulation In Mdsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytolytic function and proliferative capacities of NK cells in response to activation by cytokines are profoundly altered in MDS. 7 It has been suggested that the impairment of NK cytolytic function in MDS, which accompanies disease progression, could be restored with lenalidomide. 8 Moreover, NK alloreactivity after allo-SCT has a major role in the graft-versus-leukemia effect without causing GVHD.…”
mentioning
confidence: 99%